RANCANG BANGUN MESIN PENGERING SEPATU RAMAH LINGKUNGAN DENGAN SISTEM HEATER - Jaelani Jaelani; Sudarmono Sudarmono; Muhd Hafizal Fitri (CV. KAMPUS AKADEMIK PUBLISING, 2026)
. Environmentally friendly shoe dryer and analyze the effect of the heater heating system on shoe drying rate. The background to this research arose from the need for a faster and more hygienic shoe drying method than drying in the sun, which is often time-consuming, impractical, and has the potential to cause odors or mold. Furthermore, this design incorporates